Critical Perspectives on Nigerian Political Economy and Management - Utomi, Pat (Spectrum Books Ltd, 2000)
This book is a collection of essays on the environment of business in Nigeria. The issues critically reviewed in the essays span the spectrum of the budget process in government, banking and finance, as well as values and ethics.
Keywords: Management; Non-Fiction; Political Economy